Prevalence of the hemochromatosis gene mutation in patients with nonalcoholic steatohepatitis and correlation with degree of liver fibrosis - Zamin Jr,Idilio (2006)
BACKGROUND: Nonalcoholic steatohepatitis is a chronic liver disease with a high prevalence in the general population and a potential to evolve into cirrhosis. It is speculated that iron overload could be associated with liver injury and unfavorable progress in affected patients. AIMS: To evaluate the prevalence of mutation of the hemochromatosis gene (HFE) in patients with nonalcoholic steatohepatitis and to correlate it with histological findings in liver specimens. PATIENTS AND METHODS: Twenty-nine patients with nonalcoholic steatohepatitis were evaluated. The presence of mutation in the hemochromatosis gene (C282Y and H63D) was tested in all patients and its result was evaluated in relation to hepatic inflammatory activity, presence of fibrosis, and iron overload in the liver. The control group was composed of 20 patients with normal liver function tests and 20 patients infected with the hepatitis C virus, with elevated serum levels of aminotransferases and with chronic hepatitis as shown by biopsy. RESULTS: Mutation of the hemochromatosis gene (C282Y and/or H63D) was diagnosed in 16 (55.2%) patients with nonalcoholic steatohepatitis, in 12 (60%) patients with hepatitis C and in 8 (40%) patients with no liver disease. No association was found between the presence of mutation and inflammatory activity, nor with the presence of fibrosis in patients with nonalcoholic steatohepatitis. An association was found between the presence of mutation and the occurrence of iron overload in liver, but there was no association between liver iron and the occurrence of fibrosis. CONCLUSIONS: The findings suggest that iron does not play a major role in the pathogenesis and progression of nonalcoholic steatohepatitis, and routine tests of the hemochromatosis gene mutation in these patients should not be recommended.